2015
DOI: 10.1007/s10439-015-1328-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensified Decellularization of Equine Carotid Arteries on Scaffold Biomechanics and Cytotoxicity

Abstract: Decellularized equine carotid arteries (dEAC) are suggested to represent an alternative for alloplastic vascular grafts in haemodialysis patients to achieve vascular access. Recently it was shown that intensified detergent treatment completely removed cellular components from dEAC and thereby significantly reduced matrix immunogenicity. However, detergents may also affect matrix composition and stability and render scaffolds cytotoxic. Therefore, intensively decellularized carotids (int-dEAC) were now evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…A detailed protocol and characterization of the here-tested dEAC has been described previously by Böer et al The scaffolds were decellularized by a detergent-based approach and thoroughly characterized with respect to their residual proteins, 12,13 their biocompatibility in vitro 14,15 and in vivo 16 and their biomechanical properties. 14 It was shown that for complete removal of cellular components and a maximized biocompatibility in vitro and in vivo an intensified decellularization process was necessary. 13,14,16 Yet, biomechanical properties were maintained and the scaffold structure was preserved.…”
Section: Decellularized Equine Carotid Artery Layers As Matrix For Rementioning
confidence: 99%
See 3 more Smart Citations
“…A detailed protocol and characterization of the here-tested dEAC has been described previously by Böer et al The scaffolds were decellularized by a detergent-based approach and thoroughly characterized with respect to their residual proteins, 12,13 their biocompatibility in vitro 14,15 and in vivo 16 and their biomechanical properties. 14 It was shown that for complete removal of cellular components and a maximized biocompatibility in vitro and in vivo an intensified decellularization process was necessary. 13,14,16 Yet, biomechanical properties were maintained and the scaffold structure was preserved.…”
Section: Decellularized Equine Carotid Artery Layers As Matrix For Rementioning
confidence: 99%
“…14 It was shown that for complete removal of cellular components and a maximized biocompatibility in vitro and in vivo an intensified decellularization process was necessary. 13,14,16 Yet, biomechanical properties were maintained and the scaffold structure was preserved. 13,14 This structure comprises three distinct layers of equine carotid arteries (EAC): the outer tunica adventitia is known to display a randomized pattern, while the tunica media displays a structure based on parallel elastin fibers and the tunica intima has almost no pattern.…”
Section: Decellularized Equine Carotid Artery Layers As Matrix For Rementioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, further testing on rod-decellularized ECM scaffolds demonstrated that harsher decellularization methods had negative effects on the ECM structure and function. 193 Rod decellularization resulted in ECM scaffold distention, disruption of structural protein macromolecular structure and significantly reduced compliance. Consequently, despite the relatively encouraging effect of rod decellularization on resultant scaffold antigen content, disruption of the remaining ECM components induced by this approach has high risk of inducing innate immune and/or nonimmunogenic failure mechanisms (e.g., aneurysmal dilation).…”
mentioning
confidence: 99%